2020
DOI: 10.1111/add.14903
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of mobile phone motivational interviewing for alcohol use problems in Kenya

Abstract: Aim To test the effectiveness of a motivational interviewing (MI) intervention using the mobile phone among adults with alcohol use problems. Design A randomized clinical trial of mobile MI and standard in-person MI with 1-and 6-month follow-up, including a 1-month waitlist control followed by mobile MI. Setting A primary health center in rural Kenya. Participants Three hundred adults screening positive for alcohol use problems were randomized and received immediate mobile MI (n = 89), in-person MI (n = 65) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 75 publications
(83 reference statements)
0
69
0
Order By: Relevance
“…To ensure that impacts are sustained, researchers should consider the wider technological, human resource and health system needs .Harder et al . add to the rapidly growing literature supporting the use of digital technology to reduce heavy drinking . The authors find that motivational interviewing‐based alcohol interventions delivered by mobile phone perform as well as their face‐to‐face alternatives, at least in the short term.…”
mentioning
confidence: 88%
“…To ensure that impacts are sustained, researchers should consider the wider technological, human resource and health system needs .Harder et al . add to the rapidly growing literature supporting the use of digital technology to reduce heavy drinking . The authors find that motivational interviewing‐based alcohol interventions delivered by mobile phone perform as well as their face‐to‐face alternatives, at least in the short term.…”
mentioning
confidence: 88%
“…2 Studies measured intention to carry out HIV prevention behaviours; both found significant improvement among those in the eHealth intervention arm compared with control [42,44]. 1 Study assessed the impact of eHealth interventions on other outcomes which found that alcohol use was significantly reduced among participants in the intervention arm compared to control [24].…”
Section: Can Ehealth Technologies Improve Hiv-related Cognitive and Other Outcomes?mentioning
confidence: 99%
“…4. Only one study evaluated digital strategies for delivering substance use interventions (99) yet the feasibility of such strategies has been demonstrated for other mental disorders in Kenya (144). Moreover, the time is ripe for adopting such an approach to substance use treatment given the fact that the country currently has a mobile subscriptions penetration of greater than 90% (145).…”
Section: Interventions and Programsmentioning
confidence: 99%
“…The number of sessions ranged from one(103,107) to six (100-102,106). Most of the individual level interventions targeted harmful alcohol use (n=9)(99)(100)(101)(102)104,106,107,109,110). One study targeted khat use among men(103), while another the use of multiple substances(105).…”
mentioning
confidence: 99%
See 1 more Smart Citation